PRAKTEK MANAJEMEN KEUANGAN: SEBUAH ANALISIS SURVEI PADA UMKM DI KOTA BATAM PROVINSI KEPULAUAN RIAU - Yuwono, Wisnu (Jurnal Ecoment Global, 2020)
This study aims to identify the practical implementation of financial management and to identify the economic impact of the financial management practices on the performance of SMEs in Batam, eventually obtained the proposals of appropriate policy recommendations relating to aspects of the implementation of financial management practices. This research is descriptive analysis with case study approach in Batam, using primary data through stratified random sampling of 150 samples of SMEs. Data analysis using scoring techniques of data through SPSS version 21. The results showed that: 1) financial management practices in SMEs in Batam relatively less strong with an average value of 2,876 (scale of 5); 2) There is no significant difference between SMEs who practice financial management above average with below average against the economic impact of companies measured by the approach ROA (return on assets), but when seen from the increase in assets, 60% of SMEs conducting financial management practices above average asset value has increased; 3) The policy recommendations specifically addressed to the Office of PMP-KUKM including: a) through mentoring activities are regularly conducted every year by the Department of PMP-KUKM, b) procurement of appropriate technology system of financial accounting information for SMEs, c) motivation expansion investment for SMEs and d) to apply a minimum service standards in the field of financial management for SMEs.Keywords: SMEs, working capital, investments, financing, financial statements, accounting information systems, budgeting.